2020
DOI: 10.1007/s40430-020-2244-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to plasma channel radius determination and numerical modeling of electrical discharge machining process

Abstract: In this investigation, a single discharge of electrical discharge machining (EDM) has been simulated using finite element method (FEM) to obtain the temperature distribution on the workpiece surface. The dimensions of discharge crater on workpiece surface were calculated using temperature distribution profile, and a FEM model for material removal rate was developed for EDM process. Also, the plasma channel radius was obtained by a newly developed mathematical model and used at simulation stage. Considering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 26 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Because, the influence time of the total energy to the workpiece by working current extends by increasing of pulse-on time. In longer pulse durations, the plasma has enough time to increase its radius with an increase in pulse duration, as determined in lots of study [28]. However, the short pulses cause less vaporization from the workpiece and long pulses cause the plasma channel to expand.…”
Section: The Effects Of the Electrical Parameters On Mrrmentioning
confidence: 97%
“…Because, the influence time of the total energy to the workpiece by working current extends by increasing of pulse-on time. In longer pulse durations, the plasma has enough time to increase its radius with an increase in pulse duration, as determined in lots of study [28]. However, the short pulses cause less vaporization from the workpiece and long pulses cause the plasma channel to expand.…”
Section: The Effects Of the Electrical Parameters On Mrrmentioning
confidence: 97%
“…Especially for magnetic eld-assisted EDM process, Shabgard et al [29] also used a slightly modi ed model of their original one, including the effect of the additional magnetic eld in the differential equation of plasma expansion. Gholipoor et al [30] compared the results of the model presented by Shabgard et al [28] and showed that the calculated plasma radius values are slightly higher to those of semi-empirical models.…”
Section: Shabgard Et Almentioning
confidence: 99%
“…Figure 5a illustrates a noteworthy rise in the depth of the indentation, attributable to a rise in the duration of pulsation, aligning with an escalation in the thickness of the layer. Gholipoor et al [64] conducted a finite element simulation of the single-spark discharge process in EDM. They utilized a numerical model to investigate the effects of pulse current and duration as input parameters on the RLT of molten material in machined surface craters.…”
Section: Recast Layer Thicknessmentioning
confidence: 99%